The poultry industries of South East Asia—the need for an integrated farming system for small poultry producers - Leong, Emily; Jalaludin, Syed (Informa UK Limited, 1982)
Poultry raising in South-East Asia is largely characterized by traditional and small-scale systems of farming and operated predominantly by small and low income farmers. Generally, the poultry industries in this Region form important and progessive components of the livestock industries. The bulk of the national supplies of poultry meat and eggs in this Region is derived from the small and subsistence type farms rather than from large commercial operations. While small farmers in the Region have traditionally practised an integrated system of crop-livestock-fish farming, the need is for greater improvement in this farming pattern, on the concept of a systems approach, where the whole range of farming activities are considered. This will ensure fuller use of indigenous farm resources and family labour. It will also result in increased production and greater productivity at the small farm level. What is being sought is a fuller understanding of how integrated farming systems have worked in the past, with regard to the agro-climatic and socio-economic conditions in each country in this Region, and how they can be made more profitable and productive today.Identifying the most suitable and optimum level of integration and developing relevant activities to meet the minimum needs of each group of small farmers in various ecological areas within country and the Region, remain important and urgent tasks. In this respect, factors such as type of technological and genetic improvement, animal health coverage, fodder and feed management and institutional support need to be considered in order to meet the changing needs of the small farmers in South-East Asia.